Haemostatic Parameters in Patients with Behçet’s Disease - Juma K. Alkaabi; David Gravell; Hamood Al-Haddabi; Anil Pathare (Sultan Qaboos University Medical Journal, 2014)
Objectives: This study aimed to evaluate the cause of thrombosis in Behçet’s disease (BD) patients, since abnormalities in coagulation and fibrinolytic parameters have shown contradictory results. Methods: Haemostatic parameters were retrospectively evaluated in BD patients treated between January 2007 and January 2011 at Sultan Qaboos University Hospital, Oman. The blood samples of 35 Omani BD patients and 30 healthy controls were analysed for factor VIII:C levels, activated protein C resistance (APCR), von Willebrand factor (vWF) antigens (Ag), collagen binding and ristocetin co-factor activity (RiCoF), antithrombin (AT), protein C (chromogenic and clotting), protein S, homocysteine, tissue plasminogen activator, plasminogen activator inhibitor, plasminogen, alpha 2-antiplasmin, lupus anticoagulant and anticardiolipin and beta2-glycoprotein-1 antibodies. Results: The mean values of factor VIII:C, vWF Ag, AT and protein S were significantly higher in the patient group (P = 0.01, 0.006, 0.04 and 0.01, respectively). There was no deficiency in protein C. Screening for APCR, anticardiolipin antibodies, anti-beta2-glycoprotein-1 antibodies and lupus anticoagulant was negative and there were no differences in homocysteine levels, nor were there differences between patients with and without thrombosis. Six patients had elevated factor VIII:C levels (>150 IU/dL, P <0.02) which normalised on repeat measurements after three months. Conclusion: The elevation of factors VIII:C, vWF Ag and AT most likely represent an acute phase phenomenon. In this study, thrombophilic factors did not seem to explain thrombotic tendency. Therefore, further mechanistic studies in a larger group of patients are needed to elucidate the basis for thrombosis in BD. We hypothesise that active BD causes vasculitic endothelial perturbation with dysfunction, leading to the observed increased propensity for thrombosis.